"Mi honor bien vale tu silencio" - Manuel Gárate (Nuevo mundo - Mundos Nuevos, 2008)
During the Chilean transition to democracy, public authority had practically abandoned the subject of human right's violations, especially through the publication of Informe Rettig in 1991.  But it was enough that Augusto Pinochet was detained in London--in 1998--such that all of this recent and sensitive past would make an irruption in public space.  As a product of the denunciation of torture between two academics made public in 2001, multiple personal and institutional sensitivities emerged, installing the subject of the recent past as an unresolved matter in Chilean society.  Furthermore, we will see how the legislation about the offenses of word influenced the mediation of the case and the later creation of a national commission in order to bring to light the torture and political imprisonment in Chile.